Fast balancing method for an AC bridge based on a novel phase matching technique. Issue 3 (3rd May 2016) - Ida, Nathan; Pasdar, Amir Mehdi
Abstract : Purpose: – The purpose of this paper is to develop a method of balancing an AC bridge with minimum computation time. The applications envisioned are in power system monitoring and sensing Design/methodology/approach: – The method is based on a recursive algorithm, first matching the phase followed by that of amplitude. Each phase step requires three samples per steps.Voltage matching is based on halving the range of measured amplitudes in each step, resulting in an n-step recursive algorithm. Findings: – Computation is minimal – only requires four phase matching steps for an error of 1°. Further steps improve on this error. Matching of amplitude is equally fast. The resolution in amplitude is directly proportional to the number of steps. An example and experimental results demonstrate the efficiency of the method. Research limitations/implications: – Balancing of AC bridges in conjunction with automated measurement systems is a fairly complex process requiring either extensive computation or dedicated hardware (tunable devices, microprocessors, etc.). The current method is recursive and very light on computation. This means the method can be used in sensing systems where neither extensive hardware nor computational resources are readily available. Practical implications: – The method has been developed for power line AC impedance sensing as part of a power line monitoring system. It is however a general method that can be used in any AC bridge application. Originality/value: – The methods used as well as the implementation are entirely original. These have been developed as part of a research in instrumentation of power line monitoring.